PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA KERJA TERHADAP KINERJA PERANGKAT DESA SE-KECAMATAN CIKALONG KABUPATEN TASIKMALAYA - Agis Pebrian; Rita Tri Yusnita; Arga Sutrisna (Politeknik Negeri Ambon, 2023)
The research conducted aims to determine the simultaneous and partial influence of Transformational Leadership and Work Culture on the Performance of Village Officials in Cikalong District, Tasikmalaya Regency. The research method used is quantitative research with associative descriptive method (causality) and census approach. The population in this study was 186 employees who were village officials in Cikalong District, Tasikmalaya Regency. The sample determination technique used is Non Probability Sampling (Saturated Sampling). The type of data used is primary data obtained through the distribution of questionnaires to respondents. Data testing in this study includes validity tests, reliability tests, and classical assumption tests. The data analysis tools used are multiple linear regression, correlation coefficient, and coefficient of determination using IBM SPSS (Statitical Product and Service Solution) software Windows version 25. Based on the results of the study, it can be seen that Transformational Leadership and Work Culture simultaneously have a positive and significant effect on the Performance of Village Officials in Cikalong District, Tasikmalaya Regency. Transformational Leadership partially has a positive and significant effect on the Performance of Village Officials in Cikalong District, Tasikmalaya Regency. Work Culture partially has a positive and significant effect on the Performance of Village Apparatus in Cikalong District, Tasikmalaya Regency.